Modified nano lithium iron phosphate material as well as preparation method and application thereof
By using PSS and MOF materials for super-dispersion processing, the problem of insufficient performance of lithium iron phosphate cathode materials under high-rate discharge conditions was solved, and the efficient preparation and excellent electrochemical performance of modified nano-lithium iron phosphate materials were achieved.
Patent Information
- Application Number
- CN202411890092.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-20
AI Technical Summary
The existing lithium iron phosphate positive electrode materials have low electronic conductivity and lithium ion diffusion coefficient under high-rate discharge conditions, and there is unevenness in the doping process, difficulty in controlling the amount, and insufficient contact of reactants during the doping process. question.
The bisexual polymer cluster PSS and MOF materials are used for over -scoring treatment to enhance the compatibility of lithium iron phosphate and MOF materials, and to prepare the modified nano -iron phosphate material through ball mills and burning steps.
The modification efficiency is significantly improved, the electron density and conductivity of lithium iron phosphate materials are improved, and the cycle capacity retention rate of the battery is improved, reaching a capacity retention rate of ≥90%.
Smart Images

Figure CN119330329A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries, and specifically relates to a modified nano lithium iron phosphate material and a preparation method and application thereof. Background Art
[0002] Lithium iron phosphate (LiFePO4) cathode materials are widely used in lithium-ion batteries due to their high safety, good cycle life and relatively low cost. However, the electronic conductivity and lithium ion diffusion coefficient of this material are low, which limits its performance under high-rate discharge conditions. To address these issues, researchers have developed a variety of modification methods, including doping with high-valent metal cations and surface coating with conductive materials, to improve its conductivity and overall performance.
[0003] Although high-temperature solid-phase sintering is a commonly used method for preparing doped cathode materials, it faces some challenges, such as uneven doping, difficulty in accurately controlling the doping amount, difficulty in controlling the morphology and size, and insufficient contact of reactants. At present, organic doping raw materials have become an important direction in the research of cathode materials. Compared with inorganic doping, organic doping raw materials can not only maintain the crystal structure, but also enhance the active sites and charge distribution without destroying the original structure of the cathode material.
[0004] However, during the doping process, the organic polymer metal doping raw materials may affect the crystal structure or electrochemical performance of the positive electrode material due to dissolution problems or compatibility problems. Therefore, in order to improve the modification efficiency, the modification process of the positive electrode material needs to adopt a suitable modification process to improve the compatibility of lithium iron phosphate and the doping raw materials. Summary of the invention
[0005] The present invention provides a modified nano lithium iron phosphate material and a preparation method and application thereof to overcome the above technical problems. The method of the present invention can improve the efficiency of modifying lithium iron phosphate with organic doping raw materials, and the modified nano lithium iron phosphate material finally obtained has a good cycle capacity retention rate.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] The present invention provides a method for preparing a modified nano lithium iron phosphate material, comprising the following steps: S1. The precursor solution is super-dispersed, filtered, and dried to obtain a lithium iron phosphate precursor; The precursor solution includes lithium iron phosphate, PSS (sodium polystyrene sulfonate, CAS number: 25704-18-1) and polyethylene glycol; S2. The lithium iron phosphate precursor and the MOF material are ball-milled and calcined to obtain a modified nano lithium iron phosphate material; The MOF material is at least one of a titanium-containing MOF material, an aluminum-containing MOF material, and a zirconium-containing MOF material.
[0008] In the present invention, PSS is a kind of amphiphilic polymer copolymer, and its role is mainly reflected in two aspects. First, PSS is combined with the surface of lithium iron phosphate through ultra-dispersion technology, and then doped with MOF material. This process can significantly enhance the compatibility between MOF material and lithium iron phosphate. Secondly, PSS itself has good mechanical properties. When its solution is ultra-dispersed, it can provide a uniform and stable substrate for organic MOF, which helps to play a more effective doping role. In addition, PSS also has excellent dispersion effect, which can effectively prevent the agglomeration of lithium iron phosphate particles.
[0009] In S1, the precursor solution includes the following raw materials in parts by mass: 50 parts of lithium iron phosphate, 2 to 8 parts of PSS and 8 to 15 parts of polyethylene glycol; Preferably, the precursor solution comprises the following raw materials in parts by weight: 50 parts of lithium iron phosphate, 3-7 parts of PSS, and 9-12 parts of polyethylene glycol. Excessive addition of PSS will affect the conductivity of lithium iron phosphate.
[0010] In S1, the precursor solution is composed of the following raw materials in parts by mass: 50 parts of lithium iron phosphate, 2 to 8 parts of PSS, 8 to 15 parts of polyethylene glycol and 50 to 100 parts of water.
[0011] In S1, the polyethylene glycol is PEG200, PEG400 or PEG600, preferably PEG400.
[0012] In S1, the drying method is conventional in the art, preferably vacuum drying.
[0013] In S1, the lithium iron phosphate is obtained after pretreatment of the lithium iron phosphate raw material; wherein the pretreatment step comprises: aging the lithium iron phosphate raw material in a phosphoric acid solution, filtering, and sintering to obtain the lithium iron phosphate.
[0014] Further in S1, D50 of the lithium iron phosphate raw material is 0.3-0.5 μm.
[0015] Further in S1, the concentration of H3PO4 in the phosphoric acid solution is 60-70wt%.
[0016] Further in S1, the aging time is 1 to 5 hours.
[0017] Further in S1, the sintering temperature is 200-280°C.
[0018] Further in S1, the sintering time is 15 to 30 minutes.
[0019] In S1, the equipment used for superdispersion is a high-pressure homogenizer or a high-speed shear emulsifier.
[0020] In S1, the superdispersion time is 20 to 40 minutes.
[0021] Further in S1, the ultra-dispersion process of the high-pressure homogenizer is a conventional process in the art. Preferably, the working pressure of the high-pressure homogenizer is 1000-3000 psi.
[0022] Further in S1, the ultra-dispersion process of the high-speed shear emulsifier is a conventional process in the art, and the rotation speed of the high-speed shear emulsifier is 2000~5000rpm.
[0023] In S2, the ball milling process is conventional in the art.
[0024] In S2, the rotation speed of the ball mill is 300-500 rpm.
[0025] In S2, the ball milling time is 4 to 10 hours.
[0026] In S2, the ball-to-material ratio of the ball mill is 4-5:1.
[0027] In S2, the ball milling further includes a drying step, and the drying process is a conventional process in the art. Preferably, the drying method is a vacuum drying method; the drying temperature is 110-180°C, and the drying pressure is 10-30Pa.
[0028] In S2, the mass ratio of the lithium iron phosphate precursor to the MOF material is 100:4-10, preferably 100:6-8.5.
[0029] In S2, the titanium-containing MOF material is NTU-9 (CAS No.: 1586824-43-2).
[0030] In S2, the aluminum-containing MOF material is CAU-10 (CAS No.: 1416330-84-1) or CAU-21 (CAS No.: 2095465-85-1).
[0031] In S2, the zirconium-containing MOF material is UIO-66-F4 (CAS No.: 2170275-20-2) or UIO-66-F2 (CAS No.: 1458048-16-2).
[0032] In S2, the calcination temperature is 450-550°C.
[0033] In S2, the nitrogen flow rate during calcination is 5-15 L / min.
[0034] In S2, the calcination time is 3 to 10 hours.
[0035] In S2, the heating rate during the calcination process is 1-5°C / min, preferably 1-3°C / min. The slower heating rate can firstly ensure the discharge of moisture and other gas impurities. On the other hand, since the present invention uses MOF materials for doping, doping can be achieved at a lower temperature, and efficient modification can be performed without high temperature.
[0036] The invention also discloses a modified nano lithium iron phosphate material prepared by the preparation method of the modified nano lithium iron phosphate material.
[0037] As mentioned above, the modified nano lithium iron phosphate material is used in lithium batteries.
[0038] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0039] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention uses an amphiphilic polymer copolymer PSS to improve the compatibility of lithium iron phosphate and MOF materials, thereby greatly improving the modification efficiency. PSS not only has good mechanical properties and can provide a stable substrate for organic dopants, but also has excellent dispersibility and can effectively prevent the agglomeration of lithium iron phosphate particles. The modification of MOF materials can increase the electron density and conductivity of lithium iron phosphate materials and improve the overall performance of the battery.
[0040] 2. The present invention disperses PSS on the surface of lithium iron phosphate through super dispersion technology to enhance the binding property between PSS and lithium iron phosphate. At the same time, the present invention also explores the ratio of PSS and lithium iron phosphate, with the aim of making the modified nano lithium iron phosphate material have a high capacity retention rate.
[0041] 3. Compared with the direct mixed doping modification method, the lithium iron phosphate raw material processing method of the present invention can more efficiently modify the lithium iron phosphate positive electrode material and achieve a higher modification efficiency. Finally, the modified nano lithium iron phosphate material of the present invention was tested for cycle stability at 5C. After 600 cycles, the capacity retention rate was still ≥90%, and in some preferred embodiments, it was 91.5~92.5%. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the SEM image of the modified nano lithium iron phosphate material of Example 1.
[0043] Figure 2 This is the EDS image of the modified nano lithium iron phosphate material of Example 1.
[0044] Figure 3This is the SEM image of the modified nano lithium iron phosphate material of Comparative Example 1.
[0045] Figure 4 This is the SEM image of the modified nano lithium iron phosphate material of Comparative Example 2. DETAILED DESCRIPTION
[0046] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and carefully in combination with preferred embodiments below, but the protection scope of the present invention is not limited to the following specific embodiments.
[0047] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0048] The lithium iron phosphate raw materials of the following embodiments and comparative examples are sourced from Hunan Yuneng Electric Energy Battery Materials Co., Ltd., the raw material D50 = 0.4 μm, and the raw material is prepared by a high-temperature solid phase method; the lithium iron phosphate raw material is aged in a phosphoric acid solution (65 wt % H3PO4 aqueous solution) for 3 h and then filtered, and lithium iron phosphate is obtained after sintering at 250°C for 30 min.
[0049] The PSS used in the following examples and comparative examples is sodium polystyrene sulfonate (CAS No.: 25704-18-1, Mw is 80,000), purchased from Hubei Bojie Biotechnology Co., Ltd.; MOF materials were purchased from Shanghai Kaishu Chemical Technology Co., Ltd.; polyethylene glycol PEG400 was purchased from Guangzhou Jiyuan Chemical Co., Ltd.
[0050] Example 1 Preparation of precursor solution: The precursor solution is composed of 50 parts of lithium iron phosphate, 5.4 parts of PSS, 9 parts of polyethylene glycol and 90 parts of water by mass. The precursor solution is mixed.
[0051] S1. The precursor solution was super dispersed by a high-pressure homogenizer for 30 minutes, filtered, and vacuum dried at 150°C and 20Pa for 5 hours to obtain a lithium iron phosphate precursor; the working pressure of the high-pressure homogenizer was 2000psi; S2. By mass, 100 parts of lithium iron phosphate precursor and 6.7 parts of MOF material were ball-milled and dried, and then heated to 500°C at a heating rate of 2°C / min and calcined for 4h, and then cooled in the furnace to obtain a modified nano lithium iron phosphate material; In this embodiment, the ball milling speed is 400 rpm, the ball milling time is 5 h, and the ball-to-material ratio of the ball milling is 5:1; The MOF materials were 3.4 parts CAU-10 and 3.3 parts NTU-9.
[0052] The SEM image of the modified nano lithium iron phosphate material prepared in this embodiment is shown in Figure 1 , EDS diagram see Figure 2 .
[0053] Example 2 The difference between the embodiment and embodiment 1 is: The precursor solution consists of 50 parts of lithium iron phosphate, 7 parts of PSS, 12 parts of polyethylene glycol and 100 parts of water by mass; the other steps and parameters are the same as those in Example 1.
[0054] Example 3 The difference between this embodiment and embodiment 1 is that: The precursor solution consists of 50 parts of lithium iron phosphate, 4.5 parts of PSS, 10.7 parts of polyethylene glycol and 100 parts of water by mass; the other steps and parameters are the same as those in Example 1.
[0055] Example 4 The difference between this embodiment and embodiment 1 is that: By mass, 100 parts of lithium iron phosphate precursor and 7.4 parts of MOF material were ball milled; The MOF materials are 3.0 parts of CAU-10, 3.0 parts of NTU-9, and 1.4 parts of UIO-66-F4; the other steps and parameters are the same as in Example 1.
[0056] Example 5 The difference between this embodiment and embodiment 1 is that: The ultra-dispersion was carried out using a high-speed shear emulsifier with a rotation speed of 2500 rpm; the other steps and parameters were the same as those in Example 1.
[0057] Comparative Example 1 The difference between this comparative example and Example 1 is: S1. The precursor solution was stirred at 250 rpm for 5 min and then filtered, and the other steps and parameters were the same as those in Example 1. The SEM image of the modified nano-lithium iron phosphate material prepared in this comparative example is shown in Figure 3 .
[0058] Comparative Example 2 The difference between this comparative example and Example 1 is: The precursor solution does not contain PSS, and the other steps and parameters are the same as those in Example 1. The SEM image of the modified nano-lithium iron phosphate material prepared in this example is shown in Figure 4 .
[0059] Comparative Example 3 The difference between this comparative example and Example 1 is: The precursor solution consists of 50 parts of lithium iron phosphate, 10 parts of PSS, 9 parts of polyethylene glycol and 90 parts of water; the other steps and parameters are the same as those in Example 1.
[0060] Comparative Example 4 The difference between this comparative example and Example 1 is: The mass ratio of lithium iron phosphate precursor and MOF material is 100:12.
[0061] Comparative Example 5 The difference between this comparative example and Example 1 is: The heating rate during the calcination process was 8°C / min; the other steps and parameters were the same as in Example 1.
[0062] Application Examples The modified nano lithium iron phosphate materials prepared in the above examples and comparative examples are prepared into button-type half-cells, and the preparation steps are as follows: (1) Adding a solvent of N-methylpyrrolidone (NMP) to a modified nano lithium iron phosphate material, acetylene black and polyvinylidene fluoride in a mass ratio of 8:1:1 to adjust the viscosity to 4000-8000 mPa·s to prepare a positive electrode slurry; (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sheared to obtain a positive electrode sheet containing a positive electrode film layer.
[0063] (3) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to make a button half-cell.
[0064] The button half-cell was activated at 0.1C for three cycles in the voltage range of 2.0V-3.8V using Blue Electric equipment, and then a cycle stability test was performed at 5C (measured at 25°C). The test results of the battery capacity retention rate after 600 cycles are shown in Table 1 below.
[0065]
[0066] The above embodiments and comparative examples are combined with Table 1 to show that: In Comparative Example 1, the precursor solution was only mixed and used without ultra-dispersion treatment. Compared with Example 1, the modified nano lithium iron phosphate material obtained in Comparative Example 1 had a larger particle size, poor dispersibility (agglomeration occurred), and a low capacity retention rate. This is because the ultra-dispersion method not only improves the modification efficiency of PSS, but also enables PSS to fully play the role of a dispersant.
[0067] In Comparative Example 2, the precursor solution does not contain PSS, resulting in direct modification of lithium iron phosphate and MOF materials. The final modified nano lithium iron phosphate material has a low capacity retention rate, which also shows that the direct MOF doping modification method is inefficient. Figure 4 It can be seen that when PSS is not added, the overall particle size of the modified nano-lithium iron phosphate material will also be larger.
[0068] In Comparative Example 3, excessive PSS content will affect the electrochemical performance of lithium iron phosphate. This may be because -SO3 - The groups interfere with the crystal structure of lithium iron phosphate and increase the roughness of the surface of lithium iron phosphate, thereby reducing the contact area between the positive electrode material and the electrolyte.
[0069] In comparative example 4, excessive addition of MOF material will result in a too thick carbon layer during calcination, affecting the stability and cycle life of the material. In addition, excessive MOF material may also cover the active sites of lithium iron phosphate, resulting in a reduced utilization rate of the active material.
[0070] In comparative example 5, a too high heating rate will lead to two problems: first, the impurity removal during the calcination process is incomplete, and second, it is not conducive to the full doping of the MOF material. Both factors may affect the performance of the final material.
[0071] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0072] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing modified nano lithium iron phosphate material, characterized in that: The following steps are involved: S1. The precursor solution is super-dispersed, filtered, and dried to obtain a lithium iron phosphate precursor; S2. The lithium iron phosphate precursor and the MOF material are ball-milled and calcined to obtain a modified nano lithium iron phosphate material; The precursor solution includes lithium iron phosphate, PSS and polyethylene glycol; The MOF material is at least one of a titanium-containing MOF material, an aluminum-containing MOF material, and a zirconium-containing MOF material.
2. The method for preparing the modified nano lithium iron phosphate material according to claim 1, characterized in that: The precursor solution includes the following raw materials in parts by weight: 50 parts of lithium iron phosphate, 2 to 8 parts of PSS and 8 to 15 parts of polyethylene glycol.
3. The method for preparing the modified nano lithium iron phosphate material according to claim 1, characterized in that: The lithium iron phosphate is obtained after pretreatment of the lithium iron phosphate raw material; wherein the pretreatment step comprises: aging the lithium iron phosphate raw material in a phosphoric acid solution, filtering, and sintering to obtain the lithium iron phosphate.
4. The method for preparing the modified nano lithium iron phosphate material according to claim 3, characterized in that: Meet at least one of the following conditions ①~⑥: ① The D50 of the lithium iron phosphate raw material is 0.3-0.5 μm; ② The concentration of H3PO4 in the phosphoric acid solution is 60-70wt%; ③ The aging time is 1 to 5 hours; ④ The sintering temperature is 200-280°C; ⑥The sintering time is 15 to 30 minutes.
5. The method for preparing the modified nano lithium iron phosphate material according to claim 1, characterized in that: The equipment used for the super-dispersion is a high-pressure homogenizer or a high-speed shear emulsifier.
6. The method for preparing the modified nano lithium iron phosphate material according to claim 1, characterized in that: The mass ratio of the lithium iron phosphate precursor to the MOF material is 100:4-10.
7. The method for preparing the modified nano lithium iron phosphate material according to claim 1, characterized in that: Meet at least one of the following conditions ①~③: ① The titanium-containing MOF material is NTU-9; ② The aluminum-containing MOF material is CAU-10 or CAU-21; ③The zirconium-containing MOF material is UIO-66-F4 or UIO-66-F2.
8. The method for preparing the modified nano lithium iron phosphate material according to claim 1, characterized in that: Meet at least one of the following conditions ①~④: ① The calcination temperature is 450~550℃; ② The nitrogen flow rate during calcination is 5~15L / min; ③ The calcination time is 3 to 10 hours; ④ The heating rate during the calcination process is 1~5℃ / min. 9 . The modified nano lithium iron phosphate material prepared by the method for preparing the modified nano lithium iron phosphate material according to claim 1 .
10. Use of the modified nano lithium iron phosphate material according to claim 9 in lithium batteries.
Citation Information
Patent Citations
Preparation method for negative electrode material of lithium iron phosphate battery
CN106654208A
Positive electrode material for sodium-ion battery and preparation method of positive electrode material
CN112447947A
Modified positive electrode for high-voltage lithium ion battery and preparation method of modified positive electrode
CN113809329A
Preparation method of lithium iron phosphate battery positive electrode material
CN116812899A
Magnetohydrodynamic electric power generator
TW201841458A
Cited By
Lithium iron phosphate positive electrode material and preparation method and application thereof
CN121536896A